Effect of hBN/Al2O3 nanoparticles on engine oil properties - Abdullah, Muhammad Ilman Hakimi Chua; Abdollah, Mohd Fadzli bin; Amiruddin, Hilmi; Mat Nuri, Nur Rashid; tamaldin, noreffendy; Hassan, Masjuki; Saleman, Abdul Rafeq (2014)
This paper provides oil properties study of conventional diesel engine oil enriched with hBN/Al2O3 nanoparticles. In this study, an optimal composition (0.5 vol.%) of 70nm hBN and Al2O3 nanoparticles separately dispersed in SAE 15W40 diesel engine oil by sonication technique. The oil properties were studied by measuring the Viscosity Index (VI), Total Acid Number (TAN), Total Base Number (TBN) and flash point temperature. In addition, the stability of nanoparticles in oil was also observed by measuring the absorption value over time using ultraviolet (UV) spectrometer. The results reveal that the nano-oil with hBN nanoparticles could improves or at least maintain the key lubrication properties, though the TAN value is slightly increased. In addition, the dispersion of nano-oil was stable up to 168 hours before the sedimentation occurs. The dispersion of nano-oil with hBN nanoparticles is better than that of nano-oil with Al2O3 nanoparticles. The results presented here may facilitate improvements in the conventional diesel engine oil properties performance.